Desain Alat Pemacu Pertumbuhan dan Produktivitas Sayuran Berbasis Sonic Bloom dan Cahaya Monokromatik - Joko Prasetyo; Danar Wicaksono (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2019)
Various varieties of plants thrive in Indonesia, one of which is vegetable commodities. One of the methods of vegetable planting used by farmers is to use a screen house or green house to reduce the occurrence of pests and diseases caused by high rainfall and humidity. One solution to this problem is to increase the level of agricultural productivity in Indonesia, but many problems are now being faced by farmers, namely agricultural land is decreasing, the number of pests, the decline in crop yields. The technology used is electroculture where plants will be stimulated or given a stimulus using monochrome light and high frequency audio. High frequency sounds trigger cells in plants to accelerate metabolic circulation and monochrome light is used to replace sunlight at night so that the period of photosynthesis becomes longer. Based on the results of the study, it was found that the plants tested could grow and bear fruit faster than normal conditions. In this study using pakcoy plants. The increase that occurred in pakcoy plants with this technology was 40.08%, so using this tool could increase crop yields.